(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article discusses the issues of effective mastering of the Latin language and the basics of medical terminology in higher medical educational institutions. In particular, the linguistic features of terminological units imported from Latin and Greek in the process of studying medical terms, their structure and semantic layers are analyzed. The importance of teaching Latin and Greek doublets in the formation of professional competence in students, modern methodological approaches and interactive methods used in their teaching are also considered. The article discusses a system of exercises aimed at developing the skills of applying medical terminology in practice, along with the theoretical mastery of medical terminology. It also analyzes pedagogical technologies that serve to improve students’ language competence, ensure the effectiveness of memorizing and correctly using terms. This approach serves to develop the professional speech culture of students studying in the medical field and adapt them to the international medical terminology system.